Islamic Communication Principles as a Framework for Cultural Transformation: Ethical Integration in Contemporary Social Contexts - Arianto, Nanang; Hasibuan, Rial Sukma; Desiana, Desiana; Hasibuan, Susanti (Ishlah: Jurnal Ilmu Ushuluddin, Adab dan Dakwah, 2025)
This article aims to analyze the principles of Islamic communication as an ethical and strategic framework in supporting cultural transformation amidst modern social challenges. This study uses a qualitative method with a library research approach, reviewing various literature on Islamic communication and cultural change. The results of the study indicate that eight main principles of communication—clarity, openness, relevance, humility, respect, homophily, heterophily, and acculturation—have a significant contribution in creating ethical, inclusive, and contextual communication patterns. These principles are rooted in Islamic values ​​and are manifested in six speech styles (qaulan) mentioned in the Qur'an, namely: qaulan sadida, baligha, ma'rufa, karima, layyinan, and maysura. This article offers an integrative approach that not only places the principles of Islamic communication as a guideline for da'wah, but also as a cultural strategy that can accommodate the dynamics of multicultural society and the digital era. The implications of this study indicate that Islamic communication can be a transformative instrument that encourages just and civilized social change. This study recommends further field-based studies to explore the implementation of these principles in real life, especially in contemporary religious, educational, and da'wah media institutions. Artikel ini bertujuan untuk menganalisis prinsip-prinsip komunikasi Islam sebagai kerangka etis dan strategis dalam mendukung transformasi budaya di tengah tantangan sosial modern. Penelitian ini menggunakan metode kualitatif dengan pendekatan studi pustaka (library research), mengkaji berbagai literatur tentang komunikasi Islam dan perubahan budaya. Hasil kajian menunjukkan bahwa delapan prinsip utama komunikasi—kejelasan, keterbukaan, relevansi, kerendahhatian, penghormatan, homofili, heterofili, dan akulturasi—memiliki kontribusi signifikan dalam menciptakan pola komunikasi yang etis, inklusif, dan kontekstual. Prinsip-prinsip ini berakar dari nilai-nilai Islam dan terwujud dalam enam gaya tutur (qaulan) yang disebutkan dalam Al-Qur’an, yaitu: qaulan sadida, baligha, ma’rufa, karima, layyinan, dan maysura. Artikel ini menawarkan pendekatan integratif yang tidak hanya menempatkan prinsip komunikasi Islam sebagai pedoman dakwah, tetapi juga sebagai strategi kultural yang mampu mengakomodasi dinamika masyarakat multikultural dan era digital. Implikasi dari penelitian ini menunjukkan bahwa komunikasi Islam dapat menjadi instrumen transformatif yang mendorong perubahan sosial yang adil dan beradab. Penelitian ini merekomendasikan studi lanjut berbasis lapangan untuk menggali implementasi prinsip-prinsip tersebut dalam kehidupan nyata, khususnya di lembaga keagamaan, pendidikan, dan media dakwah kontemporer.